WHAT MATTERS MOST TO PATIENTS BEFORE AND AFTER DIAGNOSIS OF THYROID DYSFUNCTION? - MY, Yap; M, Mohd Azril; CP, Ooi; A, Abdul Hanif Khan; A, Rosliza; M, Norlaila; S, Norlela; K, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Thyroid dysfunction (TD) has a prevalence of 3.4% in Malaysia. Although there are significant disparities in quality of life before and after diagnosis in many diseases, no study has been done to assess the impact of TD on patients before and after diagnosis. Thus, the objective of this analysis is to evaluate what matters most to patients before and after diagnosis of TD. METHODOLOGY This qualitative study utilised a Malay language version of the semi-structured interview guide in Malaysia. This is part of the larger research developed from interactive discussions with patients who have thyroid dysfunction. Data were collected using a dual-method approach, i.e.: face-to-face in-depth interviews in the endocrine clinic and online survey using the same set of questions in the interview guide. We analysed the responses guided by the question: What are the differences in patient experience and perspective before and after diagnosis of TD? RESULTS Responses from 96 patients were analysed. Most (>50%) patients had symptoms associated with TD, and a minority (15%) experienced neck swelling. These patients were unaware that their experience is related to TD. After being informed of the diagnosis of TD, 95% of patients are worried and burdened by the disease. Poor knowledge of the disease, treatment, and uncertainties of the progression of TD aggravated the emotion. CONCLUSION This analysis showed that the diagnosis of TD placed a significant burden on patients’ lives. Our findings of the experience before and after diagnosis of TD provided a focus to address patient concerns. Thus, we need more research to provide insight into the patients’ experiences and perspectives for developing management and support programmes in thyroid care.